2023
DOI: 10.1002/agt2.401
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐dependent aggregation‐enhanced photoacoustic of atomically precise metal nanocluster

Abstract: Atomically precise metal nanoclusters (MNCs), as a potential type of photoacoustic (PA) contrast agent, are limited in application due to their low PA conversion efficiency (PACE). Here, with hydrophilic Au25SR18 (SR = thiolate) as model NCs, we present a result that weakly polar solvent induces aggregation, which effectively enhances PA intensity and PACE. The PA intensity and PACE are highly dependent on the degree of aggregation, while the aggregation‐enhanced PA intensity (AEPA) positively correlates to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Aggregation-induced emission (AIE) often observed in CuNCs enhances the emission brightness, structural stability, and sensitivity of CuNCs-assembled solids. 16,17 electrochemical 18,19 and luminescence 20,21 responses. A recent report from our group demonstrated that cobalt NCsassembled plates detect As 3+ in water electrochemically, with high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregation-induced emission (AIE) often observed in CuNCs enhances the emission brightness, structural stability, and sensitivity of CuNCs-assembled solids. 16,17 electrochemical 18,19 and luminescence 20,21 responses. A recent report from our group demonstrated that cobalt NCsassembled plates detect As 3+ in water electrochemically, with high sensitivity and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Affordability in the field is an important criterion, especially in resource-limited situations. Aggregation-induced emission (AIE) often observed in CuNCs enhances the emission brightness, structural stability, and sensitivity of CuNCs-assembled solids. , Some reports on metal NCs based sensors for As detection are available, explicitly involving electrochemical , and luminescence , responses. A recent report from our group demonstrated that cobalt NCs-assembled plates detect As 3+ in water electrochemically, with high sensitivity and selectivity .…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, stimulus-responsive luminescent materials have received wide attention because of their “smart” characteristics, whereby the emitted intensity and color of light can be modified in response to the external stimuli, such as mechanical force, , light, pH, , cations, , and solvents. With the diversification of real-world usage scenarios, materials that exhibit fluorescence alteration induced by mechanical force (mechanofluorochromic or MFC materials) play significant roles in various practical applications, including lighting devices, mechano-sensors, memory chips, and security inks. Up to now, a considerable number of MFC materials have been reported, including oligo-oxyethylene (OOE), , (E)-9-Octyl-3-(4-(phenylsulfonyl) styryl)-9 H -carbazole (DPS-OCZ), nanoclusters, polydopamine, , and metal complexes. The photoluminescent properties of these MFC materials are highly related to their corresponding surface morphologies, , inter- and intramolecular interactions, , molecular packing modes, , and molecular geometric configurations. Upon analysis at the molecular level, similar structural features, such as lamellar layers and parallel layer structures, are observed. Consequently, when subjected to various types of mechanical force, such as grinding, crushing, stretching and so on, the molecular structures of these MFC materials easily undergo changes, leading to alterations in their emission maximum wavelength and quantum yield.…”
mentioning
confidence: 99%